Early decrease of ventilatory ratio after prone position ventilation may predict successful weaning in patients with acute respiratory distress syndrome: A retrospective cohort study - Wang, Zhichang; Xia, Feiping; Dai, Huishui; Chen, Hui; Xie, Jianfeng; Qiu, Haibo; Yang, Yi; Guo, Fengmei (Frontiers in Medicine, 2022)
Background Previous studies usually identified patients who benefit the most from prone positioning by oxygenation improvement. However, inconsistent results have been reported. Physiologically, pulmonary dead space fraction may be more appropriate in evaluating the prone response. As an easily calculated bedside index, ventilatory ratio (VR) correlates well with pulmonary dead space fraction. Hence, we investigated whether the change in VR after prone positioning is associated with weaning outcomes at day 28 and to identify patients who will benefit the most from prone positioning. Materials and methods This retrospective cohort study was performed in a group of mechanically ventilated, non-COVID ARDS patients who received prone positioning in the ICU at Zhongda hospital, Southeast University. The primary outcome was the rate of successful weaning patients at day 28. Arterial blood gas results and corresponding ventilatory parameters on five different time points around the first prone positioning were collected, retrospectively. VR responders were identified by Youden’s index. Competing-risk regression models were used to identify the association between the VR change and liberation from mechanical ventilation at day 28. Results One hundred and three ARDS patients receiving prone positioning were included, of whom 53 (51%) successfully weaned from the ventilator at day 28. VR responders were defined as patients showing a decrease in VR of greater than or equal to 0.037 from the baseline to within 4 h after prone. VR responders have significant longer ventilator-free days, higher successful weaning rates and lower mortality compared with non-responders at day 28. And a significant between-group difference exists in the respiratory mechanics improvement after prone (P < 0.05). A linear relationship was also found between VR change and compliance of the respiratory system (Crs) change after prone (r = 0.32, P = 0.025). In the multivariable competing-risk analysis, VR change (sHR 0.57; 95% CI, 0.35–0.92) was independently associated with liberation from mechanical ventilation at day 28. Conclusion Ventilatory ratio decreased more significantly within 4 h after prone positioning in patients with successful weaning at day 28. VR change was independently associated with liberation from mechanical ventilation at day 28.